Evaluation Einführung Arbeitsagogik in den Anstalten Witzwil - Schwarz, Hans-Rudolf (Über Mauern blicken - 25 Jahre Forschen im Justizvollzug: Festschrift für Ueli Hostettler zum 65. Geburtstag, 2025)
How can educational work in the prison system be strengthened without placing excessive demands on existing prison cultures? This article takes stock of the introduction of work-based educational concepts in the Witzwil institutions and shows how practical research, targeted communication, and tact and sensitivity have succeeded in winning over even skeptical staff members. (machine translation)